RE-INTERPRETASI KEABSAHAN ARAH KIBLAT MASJID KUNO - Awaludin, Muhammad (UIN ALAUDDIN MAKASSAR, 2021)
Qibla direction is one of the valid conditions in the implementation of prayer. Every Muslim is required to know the correct Qibla direction when going to pray. The study of the Qibla direction has branched out into three areas: Fiqh, Science, and Tradition. There is a considerable gap in the process and interpretation of the Qibla between science and tradition. Science talks about the straight line of Qibla direction between the Kaaba building and the mosque, while the tradition of the Qibla direction maintains the legacy of the scholars / guardians who have determined the Qibla direction as it is. So that these two understandings are enough to provide a clear limit on understanding the Qibla direction. Therefore, the author in this paper examines the validity of the Qibla direction of the ancient mosque/tradition if it is maintained. The results of the author's study state that fiqh seems to be the middle ground for these two camps. When we talk about the Qibla direction of science, we are actually talking about the Qibla direction in thecategory Ainul Kaaba. Meanwhile, if we talk about the direction of Qibla from the point of view of tradition, then in fact we are also talking about the fiqh of the Qibla direction in thecategory jihadul Kaaba